Changing User-Perspectives in a Changing Organisation of Casework for Families at Risk. Issue 5 (20th October 2018) - Villumsen, Anne Marie; Leth, Louise Austeen
Abstract : Casework with families at risk is central to modern welfare organisations, especially in view of the professional challenge involved in knowingly changing the life circumstances and development of families at risk. The aim of this article is to present and discuss how two different types of organisation (Model One and Model Two) can create two qualitatively different outlooks for families at risk. Qualitative interviews with 29 families at risk form the empirical basis for this article. These data have been subjected to a thematic analysis. The study is placed within a Developmental Evaluation methodology. Through the voices of families at risk, the article presents that, due to specialisation and task division, the different departments become blind to the complexity of the social problems and situations that surround families at risk. The organisation of our systems of support influences whether the families experience the opportunity of having authority over and influence on their lives as well as a sense of dignity. There is great learning potential within the field of practice as well as within research in giving voice to families at risk — before, during and after attempts at helping them are made.